2023
DOI: 10.1111/nph.19157
|View full text |Cite
|
Sign up to set email alerts
|

The YABBY gene SHATTERING1 controls activation rather than patterning of the abscission zone in Setaria viridis

Abstract: Summary Abscission is predetermined in specialized cell layers called the abscission zone (AZ) and activated by developmental or environmental signals. In the grass family, most identified AZ genes regulate AZ anatomy, which differs among lineages. A YABBY transcription factor, SHATTERING1 (SH1), is a domestication gene regulating abscission in multiple cereals, including rice and Setaria. In rice, SH1 inhibits lignification specifically in the AZ. However, the AZ of Setaria is nonlignified throughout, raising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(151 reference statements)
0
0
0
Order By: Relevance
“…This study nicely showed how local auxin metabolism can impact de novo organ formation. There was also a very cool study on a new role for auxin signaling in shattering, in Setaria, which has not been observed in other grass species (Yu et al, 2023). I also enjoy reading New Phytologist for its excellent science in nonmodel plants.…”
Section: Forummentioning
confidence: 99%
“…This study nicely showed how local auxin metabolism can impact de novo organ formation. There was also a very cool study on a new role for auxin signaling in shattering, in Setaria, which has not been observed in other grass species (Yu et al, 2023). I also enjoy reading New Phytologist for its excellent science in nonmodel plants.…”
Section: Forummentioning
confidence: 99%
“…In addition, these genes are responsible for maintaining the proper activity of the meristem [31,36]. YABBYs were also found in rice, maize, and wheat [37][38][39][40] and found functioning in carpel specification and leaf midrib formation [41], the development of vasculature [42], the determination of the fate of abaxial cells in leaf development and architecture [43][44][45], lateral organ development and meristem maintenance in spikelet [46][47][48], seed shattering [49,50], and the regulation of gibberellin metabolism [51]. Recently, a few studies have shown that YABBY genes are involved in abiotic stress responses, such as salt and drought stresses [52,53], cadmium (Cd) stress [54], and cold and heat stresses [55].…”
Section: Introductionmentioning
confidence: 99%